Implementation peer counselors of anti drug to prevent drug abuse in students - Pautina, Mohamad Rizal; Tuasikal, Jumadi Mori Salam; Sari, Permata; Lakdjo, Mohamad Awal; Idris, Idriani (Universitas Islam Negeri Raden Intan Lampung, 2024)
Prevention of drug abuse in students is an effort that needs to be done by the school to minimize the illicit circulation of drugs in the school environment. The goal to be achieved in this study is to determine the implications of the implementation of peer counselors on the prevention of drug abuse in students. This study used a correlation research design with two variables, namely peer counselors and drug abuse prevention. Using accidental sampling techniques, a total of 250 peer counselors from 5 high schools were obtained, then data were collected using peer counselor implementation questionnaires and drug abuse prevention questionnaires after which they were analyzed using the Pearson Product Moment correlation coefficient. The results showed a positive and significant relationship with an rxy value of 0.745 with a rtable value obtained of 0.273. This shows that the rxy value is more than the rtable value, so there is a positive and significant influence from some of the implementation of anti-drug peer counselors on the variable of prevention of anthroba abuse in students with the level of influence between some independent and some dependent, in the high category (0.61 to 0.80). The information indicates that the presence of peer counselors spread across high schools in Bone Bolango Regency plays an important role in preventing drug abuse in students.